A view of the defence strategy of Muḥarraq, a tribal town in the Gulf (poster) - al-Sulaiti, Abdulla (Proceedings of the Seminar for Arabian Studies, 2011)
This poster paper presents the defence strategy of an Arabian town, Muḥarraq (al-Muḥarraq). A war was fought around 1810 on the west coast of Qatar near the town of al-Zubārah, and as a result al-ʿUtybī fled Qatar and settled in the east coast town of Jaw (Jaww) on the island of Bahrain. However, desert nomads were determined to attack al-ʿUtybī and take control of Bahrain, which was rich in pearls, fish, and fresh water. Eventually, al-ʿUtybī found that Jaw was a relatively insecure place to protect themselves and their rich treasures and decided to move to the town of Muḥarraq. This island already had two forts and al ʿUtybī built a defensive wall on the north side of their settlement, to fortify the town from any attacks from sea or land.